2012
DOI: 10.1001/jamaoto.2013.607
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Review of Positron Emission Tomography With Contrast-Enhanced Computed Tomography in the Posttreatment Setting in Human Papillomavirus–Associated Oropharyngeal Carcinoma

Abstract: Objective To determine the value of positron emission tomography (PET) with contrast-enhanced computed tomography (CT) in assessing the need for neck dissection by retrospectively reviewing the pathology reports of patients with human papillomavirus (HPV)- associated oropharyngeal squamous cell carcinoma (SCC). Design Retrospective cohort study. Setting Tertiary medical center. Patients Seventy-seven patients with HPV-related SCC. Main Outcome Measures Seventy-seven consecutive patients with a diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 33 publications
3
31
1
Order By: Relevance
“…A high rate of complete pathological response in this group causes a lower PPV which to some extent is consistent with our findings. However, the PPV is still superior to CT [26] and more importantly, the NPV remains high which supports an observation policy regarding the neck in PET-negative patients [24].…”
Section: Discussionsupporting
confidence: 62%
“…A high rate of complete pathological response in this group causes a lower PPV which to some extent is consistent with our findings. However, the PPV is still superior to CT [26] and more importantly, the NPV remains high which supports an observation policy regarding the neck in PET-negative patients [24].…”
Section: Discussionsupporting
confidence: 62%
“…Five of the studies in Table 3 do not explain if salvage was attempted in the patients with a neck recurrence [8][9][10][11][12]. Our results following PET-CT, and most of the other studies with data on salvage rate, confirm the conclusions of our 1999 report that patients who recur in the neck after RT are unlikely to be salvaged [13].…”
Section: Salvage Of Neck Recurrencesupporting
confidence: 68%
“…Our study has the lowest PPV of 0%-meaning that we had no case in which a patient with a positive PET-CT failed in the neck. The study by Chan and colleagues reports a PPV of 15%, which is also very low [8].…”
Section: Positive Predictive Value Of Pet-ct For Residual Neck Diseasementioning
confidence: 91%
See 1 more Smart Citation
“…Chan et al (66) studied 77 patients with HPV-positive OPSCC who underwent contrast-enhanced PET/CT after radiotherapy as the primary treatment. The authors showed that enhanced PET/CT has a better negative predictive value than either enhanced CT or nonenhanced PET/CT alone in patients with HPV-positive OPSCC.…”
Section: Therapy Response Assessmentmentioning
confidence: 99%